SOSIALISASI OPERASI DAN PEMELIHARAAN IRIGASI P3A LIMBUA - Kasmawati, Kasmawati; Antaria, Sukmasari; Gaffar, Farida; Indriyanti, Indriyanti; Kasmi, Kasmi; Fadilah, Sri (Jurnal BALIRESO, 2023)
The Program for Accelerating the Improvement of Irrigation Water Use Use is one of the programs based on the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 24/Prt/M/2017 concerning General Guidelines for the Program for the Acceleration of Increasing Irrigation Water Use Use. Implementation of P3-TGAI activities in the form of repairing irrigation networks, rehabilitation of irrigation networks and improvement of irrigation networks. P3-TGAI is a program to repair, rehabilitate or improve irrigation networks based on the participation of farming communities implemented by Associations of Water-User Farmers (P3A). As for this research, it is planned to procure socialization regarding the operating and maintenance procedures of the P3A irrigation system, so that it can be utilized properly and for a long time. P3A institutions must contribute to irrigation management and be able to carry out the duties and obligations in maintaining irrigation networks. It is also expected to be able to carry out the development and management of an irrigation system properly and sustainably and be able to increase agricultural productivity and production.